Searches of Solidarity Model in the 20th Century Muslim World: From Pan-arabism to Islamic Solidarity - Mammadov, Elvusal (Scholarya Demo Journal of Ruby, 2019)
The article examines the problem of solidarity and its forms which intrigued the Muslim world in the 20th century. It emphasizes that solidarity challenges were not repetitious and monotonous, on the contrary, they possessed different content under the influence of certain political events. Initially, nationalism and pan-Arabism was chosen as the major ideologicalplatform for solidarity, however, in 1950-1970 it was gradually eroded by theideas of socialism. The nationalist solidarity failed both for internal and externalreasons and gave its place to the searches for another ideological base. From 1970s, religion became a fundamental point for solidarity challenges, advanced together with nationalism initially and appeared with the ideas of establishing solidarity drifting from nationalism after its collapse. Consequently, Islamic solidarity became topical since the 70s of the 20th century, especially after the failure of non-religious ideologies such asnationalism and socialism in the solution of the Palestinian conflict. Understanding the necessity for united activity, the government circles were concerned with a new model of solidarity and developed a solidarity model based on Islam. Historical experiences and the failure of non religious ideologies in the unification process caused Islam to play a dominant role in the solidarity of Arab-Muslim countries for the next stage. According to the author, based on the concepts of ummah and fraternity, Islamic solidarity is not theoretical and found its practicality in the activities of separate institutions established in different years.